Hungry Bengal : War, Famine and the End of Empire - Mukherjee, Janam (Oxford [England] ; New York : Oxford University Press, 2015)
Examines the interconnected events including World War II, India's struggle for independence, and a period of acute scarcity that lead to mass starvation in colonial Bengal.
Introduction : in search of famine -- War -- Denial -- Priorities -- Famine -- Japan attacks -- Second famine -- Riots -- Conclusion.
Includes bibliographical references (pages 305-316) and index.
RS Savar
Karim International
Keywords: 1900 - 1999; Famines -- India -- Bengal -- History -- 20th century; World War, 1939-1945 -- Social aspects -- India -- Bengal; Famines; Social aspects; Bengal (India) -- History -- 20th century; India -- Bengal; History